Assessment of Forward Head Posture and Ergonomics in Young IT Professionals - Reasons to Worry? - Stincel, Oana-Ruxandra; Oravitan, Mihaela; Pantea, Corina; Almajan-Guta, Bogdan; Mirica, Nicoleta; Boncu, Alexandru; Avram, Claudiu (Medicina del lavoro, 2023)
Prolonged computer use and poor ergonomics among IT professionals are considered risk factors for musculoskeletal disorders. This research aims to analyze the degree of forward head posture and workplace ergonomics in young IT professionals to assess the risk for a neck disability. Methods: A prospective study was carried out by assessing the sitting posture at work, neck disability in the cervical region, quality of life, physical activity, and ergonomics of the workspace in 73 young IT professionals (32.56±5.46 years). Results: The score for the cervical functional disability index (NDI) showed a mild neck disability (8.19±7.51). The craniovertebral angle has an average value of 32.01±11.46, corresponding to a light forward head posture, and it positively correlated with age and work experience and negatively correlated with ROSA (r=0.24, p<0.05). The NDI positively correlated with physical activity (r =00.32 p<0.05) and with ROSA (r= 0.24, p<0.05). Conclusions: In IT professionals, neck disability is associated with the lack of workspace ergonomics and the amount of physical activity. Forward head posture correlated with age, work experience, and poor workspace ergonomics. According to our findings, there are real concerns about the influence of head posture and workplace ergonomics on health among IT professionals. We consider that it is necessary to adopt preventive measures to address neck disability and improve workspace ergonomics.